Therapeutic and protective approaches to combat Campylobacter jejuni infections - Sharafutdinov, Irshad; Linz, Bodo; Tegtmeyer, Nicole; Backert, Steffen (Frontiers in Pharmacology, 2025)
Campylobacter jejuni is a typical zoonotic bacterium, colonizing the gut of many bird species as commensal. In humans, C. jejuni is a major foodborne pathogen. Infection of humans causes campylobacteriosis in the small intestine, constituting a main source of bacteria-dependent gastroenteritis cases worldwide. In particular, the ingestion of under-cooked rooster meat, raw milk and contaminated water, as well as cross-contamination of ready-to-eat food after handling raw chicken meat, are responsible for the majority of C. jejuni infections. As a consequence, infected individuals may acquire watery and/or bloody diarrhea associated with abdominal pain, and eventually post-infection illnesses of the neural system and joints, including the Guillain-Barré, Miller Fisher and Reiter syndromes. One therapeutic strategy is to reduce C. jejuni colonization in chicken farms using vaccination, bacteriocins and phage therapy protocols. Prevention approaches during poultry meat processing comprise the compliance to high hygiene standards. Furthermore, substantial progress has been also made in recent years to combat campylobacteriosis using established mouse and in vitro cell model systems. In this regard, specific C. jejuni colonization- and pathogenicity-associated components were considered as favored treatment structures, targeting bacterial movement, host cell interaction, intracellular survival, propagation and spread of the bacteria. This has been complemented by a number of pharmaceutical compounds to reduce C. jejuni-induced epithelial cell damage, inflammation and apoptosis in infected mice. Here we review these novel treatment and prevention as well as “One World - One Health” approaches that aim to diminish the consequences of acute campylobacteriosis and post-infection sequelae in humans.